2008
DOI: 10.1105/tpc.108.060426
|View full text |Cite
|
Sign up to set email alerts
|

Independent Losses of Function in a Polyphenol Oxidase in Rice: Differentiation in Grain Discoloration between Subspecies and the Role of Positive Selection under Domestication

Abstract: Asian rice (Oryza sativa) cultivars originated from wild rice and can be divided into two subspecies by several criteria, one of which is the phenol reaction (PHR) phenotype. Grains of indica cultivars turn brown in a phenol solution that accelerates a similar process that occurs during prolonged storage. By contrast, the grains of japonica do not discolor. This distinction may reflect the divergent domestication of these two subspecies. The PHR is controlled by a single gene, Phr1; here, we report the cloning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
112
5
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(123 citation statements)
references
References 72 publications
4
112
5
2
Order By: Relevance
“…Previous studies reported that Phr1 participates in the formation of black hull (Kuriyama and Kudo, 1967) and that Phr1 in japonica is a nonfunctional allele (Yu et al, 2008). We transferred the Bh4 gene into the two subspecies of cultivated rice, indica (Guangluai 4, Kasalath) and japonica (Nipponbare).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies reported that Phr1 participates in the formation of black hull (Kuriyama and Kudo, 1967) and that Phr1 in japonica is a nonfunctional allele (Yu et al, 2008). We transferred the Bh4 gene into the two subspecies of cultivated rice, indica (Guangluai 4, Kasalath) and japonica (Nipponbare).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous genetic analyses. As multiple mutations occurred in Rc (Sweeney et al, 2006) and Phr1 (Yu et al, 2008) genes, Bh4 also had multiple mutations. All three of these genes are related to color changes in grains and seeds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maekawa (1984) reported that three complementary genes, termed Bh-a, Bh-b and Bh-c, controlled the black hull phenotype. Among them, Bh-c was suggested to correspond to Phr1, which encodes polyphenol oxidase (Kuriyama and Kudo, 1967;Maekawa, 1984;Yu et al, 2008). Phr1 causes the phenol reaction-positive phenotype of seeds, in which the hull color turns black after being soaked in a phenol solution (Yu et al, 2008).…”
mentioning
confidence: 99%